Risk in the management of dental amalgam in dental medium and small entities in the department of Antioquia, Colombia - Jairo A. Ruiz; Jorge I. Pérez; Gabriel J. Gómez; María E. Carmona; Luis A. Zapata; Rosaura Carmona C (Universidad de Antioquia, 2009)
This article is based on the applied research "Environmental Management of the Dental Amalgam in Antioquia, Colombia", which was financed by the company New Stetic S. A. and the University of Antioquia. The research was carried out between 2005 and 2007 by the following groups: Biomedical Science and Technology, Precious Materials, and Pyrometallurgical and Materials Researches, and the Research and Development Division of the mentioned company. Objetive: to describe and characterize the activities about handling mercury, dental amalgam and its waste in 107 dental offices defined as medium and small, that is to say those with less than five dental chairs in the same workplace. Methodology: a poll was made in each institution filling a questionnaire about personal details of the interviewee, mercury and amalgam handling, occupational health, training, environmental conditions, and waste management. Each dental office was visited by a research engineer and an advanced engineering student who were trained in advance in order to collect the information. Results: a reflection aimed to establish integral actions and safe methodologies in the short term to promote a better quality service and a minimum risk for the people exposed to mercury and the ecosystem must be encouraged by dental and administrative staff, as well as by surveillance and control institutions and the educational institutions devoted to the formation of dental professionals.